Editorial Introduction: Contemporary Issues on Advocacy and Legal Services - Arifin, Ridwan; Niravita, Aprila (Indonesian Journal of Advocacy and Legal Services, 2025)
This editorial outlines key themes in the Indonesian Journal of Advocacy and Legal Services issue on “Contemporary Issues on Advocacy and Legal Services.” The articles examine diverse topics including restorative justice, labor regulation, digital legal counseling, and post-conflict advocacy. Case studies from Indonesia, Malaysia, and New Zealand provide comparative insights into evolving legal practices. The issue highlights ongoing challenges such as unequal access to justice, weak legal ethics enforcement, and the impact of legal pluralism. Emphasizing interdisciplinary and practical approaches, this edition contributes to advancing advocacy as a tool for legal empowerment, institutional reform, and social justice in Indonesia.